Challenges of Civil Law Enforcement on Smart Contracts in Cross-Border Transactions Based on Blockchain Technology - Safitri, Nadia Indah; Rossa, Septiana (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
With advances in blockchain technology, smart contracts have emerged as automated digital instruments for cross-border transactions. Yet, their automation and rigidity do create serious hindrances to civil law's fundamental principles, especially in terms of enforceability and dispute resolution. This research seeks to study discrepancies between the characteristics of smart contracts themselves and international civil law systems, and to unveil the legal obstacles on their path to implementation. By employing a normative juridical approach and comparative analysis from 50 legal and academic documents sourced from Indonesia, the United States, and the European Union, this research reveals regulatory divergences and the absence of a harmonized international standard. Results show that the European Union is far ahead of the United States and Indonesia in regulatory preparedness. Essentially, this research proposes a hybrid legal system, which is a combination of national and international provisions (for example, the UNCITRAL Model Law) for the establishment of blockchain-based digital dispute resolution. The outcome enlarges the horizon of digital contract law theory and serves as a handy guide for policymakers in managing legal complexities of smart contracts across jurisdictions.